The Importance Of Transitional Care In Achieving Health Reform - Naylor, Mary D.; Aiken, Linda H.; Kurtzman, Ellen T.; Olds, Danielle M.; Hirschman, Karen B. (Health Affairs, 2011)
Under the Affordable Care Act of 2010, a variety of transitional care programs and services have been established to improve quality and reduce costs. These programs help hospitalized patients with complex chronic conditions-often the most vulnerable-transfer in a safe and timely manner from one level of care to another or from one type of care setting to another. We conducted a systematic review of the research literature and summarized twenty-one randomized clinical trials of transitional care interventions targeting chronically ill adults. We identified nine interventions that demonstrated positive effects on measures related to hospital readmissions-a key focus of health reform. Most of the interventions led to reductions in readmissions through at least thirty days after discharge. Many of the successful interventions shared similar features, such as assigning a nurse as the clinical manager or leader of care and including in-person home visits to discharged patients. Based on these findings, we recommend several strategies to guide the implementation of transitional care under the Affordable Care Act, such as encouraging the adoption of the most effective interventions through such programs as the Community-Based Care Transitions Program and Medicare shared savings and payment bundling experiments. [PUBLICATION ABSTRACT]